Effects of environmental low-dose irradiation on functional-metabolic organ responses in a natural mouse population (Apodemus agrarius Pallas, 1771) within the East Urals Radioactive Trace (EURT) area, Russia. (2nd September 2022) - Orekhova, Natal´ya A.; Modorov, Makar V.
Abstract: Hypothesis: The level of radiation-induced functional metabolic reactivity can differ among organs (spleen, liver and myocardium) and reproductive-sexual groups (breeding and non-breeding under-yearlings: females and males). Materials and methods: We analyzed Apodemus agrarius individuals captured in the zone of the East Urals Radioactive Trace (EURT, Russia). In this area, concentrations are 90 Sr and 137 Cs at 10, 000 and 1000 Bq/kg, respectively, in a layer of soil not deeper than 10 cm. Comparative analysis was based on six biochemical parameters including the glycolysis level, peroxidation of lipids, H2 O2 -oxidoreductase status and concentrations of protein, DNA and RNA in tissues. Results: External and internal doses of 137 Cs and 90 Sr for A. agrarius varied by an order of magnitude, from 0.013 to 0.177 mGy/d. The level of radiation exposure was found to not differ among females but it differed between the two male reproductive groups (breeding < non-breeding under-yearlings). Sexually mature males received a significantly lower dose than females. An increase in the dose rate correlated with an increase in all biochemical indicators, thus indicating high level of tissue metabolic functions. The reproductive status of females did not affect their radiation-induced organ response rate, whereas the response to radiation of breeding males was more than 1.5-fold higher than that of non-breeding males and 2-fold higher than that of females. Conclusions: We believe that the variation of the dose load is due to migration processes: breeding males are more likely to migrate than females and therefore have less contact with radionuclides. The higher the response to radiation of breeding males can be explained by a hormonal factor: testosterone causes radiosensitivity. The reactivity of the tissues examined (myocardium < liver < spleen) develops apparently in accordance with the degree of their 'staticity' in accordance with the law of radiosensitivity of Bergonié and Tribondeau.